1987
DOI: 10.1002/tea.3660240705
|View full text |Cite
|
Sign up to set email alerts
|

A study of two measures of spatial ability as predictors of success in different levels of general chemistry

Abstract: Preliminary data (Bodner and McMillen, 1986) suggested a correlation between spatial ability and performance in a general chemistry course for science and engineering majors.This correlation was seen not only on highly spatial tasks such as predicting the structures of ionic solids (r = 0.29), but also on tasks such as multiple-choice stoichiometry questions (r = 0.32) that might not be expected to involve spatial skills. To further investigate the relationship between spatial ability and performance in introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
2
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 21 publications
6
97
2
6
Order By: Relevance
“…Students with lower visuospatial abilities 1. are unable to perform as well as their peers with higher visuospatial abilities on solving both spatial and nonspatial chemistry problems (Bodner & McMillen, 1986;Carter, LaRussa, & Bodner, 1987); 2. have difficulties reorganizing or transforming the information provided by questions into a visual representation, such as drawing preliminary figures (Pribyl & Bodner, 1987). This suggests that as using visual representations is common practice in chemistry and conceptual knowledge of chemistry is embedded in various types of molecular and symbolic representations, low spatial ability students are disadvantaged.…”
Section: Discussion and Interim Summarymentioning
confidence: 99%
See 4 more Smart Citations
“…Students with lower visuospatial abilities 1. are unable to perform as well as their peers with higher visuospatial abilities on solving both spatial and nonspatial chemistry problems (Bodner & McMillen, 1986;Carter, LaRussa, & Bodner, 1987); 2. have difficulties reorganizing or transforming the information provided by questions into a visual representation, such as drawing preliminary figures (Pribyl & Bodner, 1987). This suggests that as using visual representations is common practice in chemistry and conceptual knowledge of chemistry is embedded in various types of molecular and symbolic representations, low spatial ability students are disadvantaged.…”
Section: Discussion and Interim Summarymentioning
confidence: 99%
“…They found that students with high spatial ability appeared to have higher scores on problems that required problem-solving skills rather than rote memory or the simple algorithms such as crystal structure and stoichiometry. Correlations were stronger for verbally complex questions that required multiple steps of calculations and restructuring relevant information of the problem (Carter, LaRussa, & Bodner, 1987). Similarly, Staver and Jacks (1988) showed that students' visuospatial abilities significantly influenced their performance on balancing chemical equations.…”
Section: The Existence Of a Positive Correlation Between Spatial Abilmentioning
confidence: 94%
See 3 more Smart Citations